DESIGN OF A DECISION SUPPORT SYSTEM FOR CONTRACTOR SELECTION USING THE SAW (SIMPLE ADDITIVE WEIGHTING) METHOD. - Nurdiansyah Permana; Davit Hermawan; Raden Deden Ahmad Hidayat; Endra Abdul Hadi; Fikri Emsa Silmi (Journal of Multimedia Technology and Applied Software, 2025)
This decision support system is designed to address the problem of selecting the best contractor at PT Integrasi Kreasi Zee (Zee Studio), a crucial issue given the project's significance to the company. By implementing the Simple Additive Weighting (SAW) method, a weighted addition algorithm, this system provides a comprehensive analysis tool that enables decision-makers to solve complex problems and produce more qualified and appropriate contractor choices. The system development utilizes the Rational Unified Process (RUP) method to ensure a structured, iterative, and architecture-centered approach, thereby ensuring the resulting system functions optimally according to the company's operational needs and is easy to manage throughout its development life cycle.